Safe use of genetically modified lactic acid bacteria in food. Bridging the gap between consumers, green groups, and industry - Sybesma, Wilbert; Hugenholtz, Jeroen; de Vos, Willem M.; Smid, Eddy J. (Electronic Journal of Biotechnology, 2006)
Within the European Union (EU), the use of genetically modified organisms (GMOs) in food production is not widely applied and accepted. In contrast to the United States of America, the current EU legislation limits the introduction of functional foods derived from GMOs that may bring a clear benefit to the consumer. Genetically modified lactic acid bacteria (GM-LAB) can be considered as a different class of GMOs, and the European Union is preparing regulations for the risk assessment of genetically modified microorganisms. Since these procedures are not yet implemented, the current risk assessment procedure is shared for GMOs derived from micro organisms, plants, or animals. At present, the use of organisms in food production that have uncontrolled genetic alterations made through random mutagenesis, is permitted, while similar applications with organisms that have controlled genetic alterations are not allowed. The current paper reviews the opportunities that genetically modified lactic acid bacteria may offer the food industry and the consumer. An objective risk profile is described for the use of GM-LAB in food production. To enhance the introduction of functional foods with proven health claims it is proposed to adapt the current safety assessment procedures for (GM)-LAB and suggestions are made for the related cost accountability. A qualified presumption of safety as proposed by SANCO (EU SANCO 2003), based on taxonomy and on the history of safe use of LAB applied in food, could in the near future be applied to any kind of LAB or GM-LAB provided that a series of modern profiling methods are used to verify the absence of unintended effects of altered LAB that may cause harm to the health of the consumer.